2017
DOI: 10.1021/acs.inorgchem.7b01122
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Denser Energetic Metal–Organic Frameworks via a Tandem Anion–Ligand Exchange Strategy

Abstract: High-density materials have attracted extensive attention because of their broad applications. However, strategies for improving the densities of MOFs and preparing denser MOFs remain almost unexplored. Herein, we propose a tandem anion-ligand exchange strategy for synthesizing denser MOFs by using three-dimensional cationic MOFs (3D CMOFs) with pillared layered structures as precursors and high-density anions and small monotopic ligands as exogenous guests. By means of this strategy, we choose the high-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…IR spectra of E-PIL-H-2 and E-PIL-ONO 2 -2 showedap eak associated with the N(NO 2 ) 2 À anion ( % 1182 cm À1 ), [16] and IR spectra of E-PIL-H-3 and E-PIL-ONO 2 -3 exhibited ab and that can be attributed to the C(NO 2 ) 3 À anion ( % 1273 cm À1 ). [17] These results demonstrated the successful introduction of the three kinds of energetic anions [NO 3 À , N(NO 2 ) 2 À ,C (NO 2 ) 3 À ]i nto the PILs, respectively (see Figure S1 in the Supporting Information). In addition, elemental analysis confirmed the good purity of E-PILs (Table S1, Supporting Information).S EM images showed that the morphology of E-PIL-H-1 was composed of round-shaped nanoparticles with diameters around1 50 nm, while other E-PILs were primarily stacked with sheet structures in greaters izes ( Figure S2 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…IR spectra of E-PIL-H-2 and E-PIL-ONO 2 -2 showedap eak associated with the N(NO 2 ) 2 À anion ( % 1182 cm À1 ), [16] and IR spectra of E-PIL-H-3 and E-PIL-ONO 2 -3 exhibited ab and that can be attributed to the C(NO 2 ) 3 À anion ( % 1273 cm À1 ). [17] These results demonstrated the successful introduction of the three kinds of energetic anions [NO 3 À , N(NO 2 ) 2 À ,C (NO 2 ) 3 À ]i nto the PILs, respectively (see Figure S1 in the Supporting Information). In addition, elemental analysis confirmed the good purity of E-PILs (Table S1, Supporting Information).S EM images showed that the morphology of E-PIL-H-1 was composed of round-shaped nanoparticles with diameters around1 50 nm, while other E-PILs were primarily stacked with sheet structures in greaters izes ( Figure S2 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 74%
“…As shown in Figure , IR spectra of E‐PIL‐H‐1 and E‐PIL‐ONO 2 ‐1 showed a strong band associated with the NO 3 − anion (≈1379 cm −1 ). IR spectra of E‐PIL‐H‐2 and E‐PIL‐ONO 2 ‐2 showed a peak associated with the N(NO 2 ) 2 − anion (≈1182 cm −1 ), and IR spectra of E‐PIL‐H‐3 and E‐PIL‐ONO 2 ‐ 3 exhibited a band that can be attributed to the C(NO 2 ) 3 − anion (≈1273 cm −1 ) . These results demonstrated the successful introduction of the three kinds of energetic anions [NO 3 − , N(NO 2 ) 2 − , C(NO 2 ) 3 − ] into the PILs, respectively (see Figure S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 80%
“…In summary, we described a strategy to induce hypergolic behavior in MOFs by using acetylene and vinyl substituents to unlock the latent en-ergetic properties of electron-deficient linkers in a ZIF. This strategy also uses the formation of coordination bonds to enhance the hypergolic reactivity of the ligand, which is intrinsically different from approaches used to design other types of energetic (e.g., explosive and pyrotechnic) MOFs (19,40,41), where the formation of an extended structure often leads to ligand stabilization, in the form of reduced heat and shock sensitivity, sometimes accompanied by increased heat of detonation due to an energetic ligand being trapped in a nonpreferred conformation (31,32). The modularity of MOFs permits modification of the hypergolic properties (ID, flame color, and duration) of the fuel, including achieving ultrashort IDs, without changing its overall structure.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, high density results in higher performance. 18,42 For example, D of an explosive is proportional to its r, and P is proportional to the square of its r. 43 For an energetic material, a high value r means that more energy per unit volume can be packed into a volume-limited space, thereby yielding maximum violent explosion. The molecular volumes, uncorrected densities, and corrected densities are listed in Table 5.…”
Section: Densitymentioning
confidence: 99%